The importance of the ISO 21001:2018 standard in guaranteeing the quality of higher education - Mamatkulov, Sanjar (MMIT Proceedings, 2024)
The article examines the possibilities of the ISO 21001:2018 standard for improving the management systems of higher education institutions in our country and improving the quality of education. The contents of the ISO 21001:2018 standard, its main requirements and foreign experience regarding the practical importance of this standard are analyzed. Also, the possible consequences of applying the standards set in this document to the management system of higher education institutions operating in our country are considered, and suggestions and recommendations are given in this regard.